US CO2 emissions and IPCC components: Evidence of persistence using fractional integration - Miguel A. Martin-Valmayor; Juan Infante; Nieves Carmona-González; Luis A. Gil-Alana (Environmental and Sustainability Indicators)
This paper investigates the persistence of CO2 emissions in the US and per Intergovernmental Panel on Climate Change (IPCC) category contribution, evaluating its persistence across time (1970–2022). The structure of the integration factor and major structural breaks are examined to determine the degree of persistence across sectors and to assess policy effectiveness. Empirical results show clear evidence of persistence and non-mean reversion patterns in the long-term CO2 emissions in all sectors; though, log-data show weak mean reversion across global bioenergetic emissions and fossil manufacturing-civil airline emissions. Moreover, structural breaks results suggest that these breaks are mostly related to economic shocks rather than to environmental policies. Excepting Road and Transportation, all IPCC sectors show decreasing emission patterns since 2000. Thus, this persistent profile would suggest that emissions from these sectors would maintain this decreasing pattern in the future. However, Road and Transportation (29 % of total emissions) exhibit a different growing pattern, that suggests further increases if no additional measures are taken. Therefore, to accomplish IPCC commitments, more efforts are recommended with a special focus in the Road and Transportation sector to change the long-term US CO2 emission pattern.